DEIXIS FOR PEOPLE - Umdatul Khoirot (Jurnal Bahasa Lingua Scientia, 2015)
There are communication almost fail because of misunderstanding of the reference. Thus, explaining reference for its importance in communication is needed. Reference means pointing that is as an act in which a speaker or writer uses linguistic forms to enable a listener or reader to identify something. Reference can be divided into two: exophora and endophora. Furthermore, there two kinds of exophora: homophora and deixis. Deixis is a form of referring that is tied to the speaker´s context. In addition, deixis concerns the way in which languages encode or grammaticalize features of the context of utterance or speech event, and this also concerns ways in which in the interpretation of utterances depends on the analysis of that context of utterance.